Disparities in gastric emptying and postprandial glycaemia between Han Chinese and Caucasians with type 2 diabetes. (January 2020) - Wang, Xuyi; Xie, Cong; Marathe, Chinmay S.; Malbert, Charles-Henri; Horowitz, Michael; Jones, Karen L.; Rayner, Christopher K.; Sun, Zilin; Wu, Tongzhi
Abstract: Aims: Gastric emptying is a major determinant of postprandial glycaemia in both health and type 2 diabetes (T2DM); the potential impact of ethnicity on gastric emptying is unclear. We compared the rate of gastric emptying of a standardised meal and the associated glycaemic response in Han Chinese and Caucasian patients with T2DM. Methods: 14 Han Chinese and 14 Caucasian T2DM patients, managed by diet and/or metformin monotherapy, underwent concurrent measurements of gastric emptying and blood glucose for 240 min after a 99mTc-calcium phytate-labelled mashed potato meal. Results: Han Chinese patients were slightly younger (P < 0.05), and had a lower BMI (P < 0.05), than Caucasians. There were no differences in either HbA1c or fasting blood glucose between them. Gastric half-emptying time (T50) was shorter (P < 0.05) and the postprandial blood glucose increment greater (P < 0.05) in Han Chinese than Caucasian patients. Both the increment in blood glucose from baseline at 60 min and peak blood glucose were related inversely to T50 (P < 0.05 each). Conclusions: Han Chinese with relatively well-controlled T2DM have more rapid gastric emptying compared to Caucasians, which is associated with a greater postprandial glycaemic excursion. These differences may inform the choice of management, e.g. Han Chinese may particularly benefit from therapies that slow gastric emptying.